miR-144 delivered by nasopharyngeal carcinoma-derived EVs stimulates angiogenesis through the FBXW7/HIF-1α/VEGF-A axis - Xiaoyan Tian; Yuehui Liu; Zhi Wang; Shuhong Wu (Elsevier, 2021)
The current study aimed to explore the role of tumor-derived extracellular vesicles (EVs) in angiogenesis during nasopharyngeal carcinoma (NPC). NPC biopsy specimens were initially collected. Human umbilical vein endothelial cells (HUVECs) were co-cultured with EVs isolated from NPC cells, after which their migration, invasion, as well as vessel-like tube formation were evaluated by Transwell chamber systems and Matrigel-based angiogenesis assays. The pro-angiogenic activities of EVs as well as the candidate microRNA (miRNA or miR) were examined using an in vivo Matrigel angiogenesis model. The results indicated that the levels of miR-144 in the NPC tissues were upregulated when compared to the nasopharyngeal normal tissues in addition to the identification of a positive correlation with the expression of CD31. Moreover, our data indicated that miR-144 was highly enriched in EVs from NPC cells and then ultimately enhanced the migration and invasion of HUVECs and vessel-like tubes in vitro and in vivo. Notably, miR-144 was identified as a mediator in NPC-EV-induced regulatory effects through the inhibition of the target gene FBXW7 and promotion of the transcriptional factor HIF-1α-dependent vascular endothelial growth factor (VEGF-A). Taken together, the key findings of the current study highlighted the role of miR-144 as an extracellular pro-angiogenic mediator in NPC tumorigenesis.